The 28-Day Vitality Plan - Selby, Anna (London Hamlyn, 1999)
This diet and workout plan aims to help you cleanse your system and tone your body in 28 days. Containing a week-by-week make-over with suggestions for cleansing the body of toxins, it also introduces a healthier diet and exercise regime. A personal progress, weight and height chart is included.
Include colour illustrations and index
Designed by Gerrish, Peter
Keywords: Low-calorie diet -- Salads -- Exercise